(untitled) (Eurasian Journal of Philology Science and Education, 2020)
In the present article the author raises the topic of Eastern protographs, which at one time were sources for ancient Russian historical works. These works contain a certain number of references and direct quotations from “Eastern” stories. Some of these protographs and sources can be referred to Turkic. The problem of the former Turkic domination and influence on the peoples of Eastern Europe is traditionally avoided by many domestic historians. A number of chronicle terms of Altai origin are sometimes interpreted as “cryptography”, “error” or “European borrowing”. Meanwhile, the correct reading of individual terms or entire phrases can significantly correct and even change the meaning of the work. On the example of a limited number of medieval works in this article, the author gives examples of the use of Turkic languages for a more accurate perception of the primary meaning of the ancient work. Already the first legendary information about the initial stage of the old Russian statehood can get a different interpretation or direction when taking into account the Turkic influence on the formation of Eastern European cultures. So the name Oleg could well be part of the title, as is often the case in world history, and the dynasty of Russian princes in accordance with the information of some Chronicles, included (Avar) Kagan. Legends of the Russian people has preserved the memory of the heroes: Bulgarian Khan Asparuh (father of Rus), knight Bulat, Sukhmani, Cudeare etc. The greatest influence was made by the culture of the State of the Juchids (“Golden Horde”). Thus, the Horde source is revealed in the analysis of the episode of the about the beginning of the “Great Troubles”, the turnovers “the Words about Igor’s regiment” are specified, the orientation of “the Legend about Mamayev’s slaughter” changes, another meaning gets “the Story about the ruin of Moscow by Tokhtamysh-Tsar”. In spite of the fact that not all known cases of application of Turkism are given in the article, the author comes to a natural conclusion about the great scientific importance of this direction in textual and source studies and the need to study the basics of the Turkic language by Historians-Medievalists. Thus, the new knowledge is presented in the article not only in revealing the true meaning of an episode, but also in recognizing the Turkic influence on Russian written culture as a long-term process.